SUN-517 Postoperative Hypoparathyroidism Treated With Teriparatide In Apatient With Malabsorption Due To Celiac Disease: A Case Report And Literature Review - Khan, Mehr (J Endocr Soc, 2019)
A 31 year-old female with a past medical history of preeclampsia and non-toxic multinodular goiter causing compressive symptoms underwent total thyroidectomy. A large parathyroid gland was noted and removed during surgery. Hyperparathyroidism was not suspected preoperatively, (preoperative calcium levels were 8.4 mg/dL) and the patient did not have calcium, PTH, or Vitamin D level determination prior to having thyroidectomy. Final pathology showed a 49.5 gm thyroid gland containing multiple benign nodules. Two parathyroid glands were identified. A few hours postoperatively she developed symptomatic hypocalcemia (Ca level 7.8) and required IV calcium supplementation as her calcium levels could not be maintained in the recommended range using oral calcium. Her supplemental therapy requirements reached oral calcium carbonate 7500 mg every 6 hours, IV calcium gluconate at a rate of 750 mg/hr, calcitriol 1 mcg every 6 hours, oral magnesium 800 mg twice daily, and HCTZ 50 mg daily. It was then that teriparatide 20 mcg subcutaneously was initiated twice daily (based on recommendations found in references (1 -2)). With the initiation of teriparatide, she became independent of IV calcium gluconate. At this time the patient disclosed that she had been suffering from diarrhea for the preceding 11 months prior to thyroid surgery. After consultation with GI she underwent biochemical confirmation, colonoscopy and EGD with duodenal biopsies, which demonstrated celiac disease. Colon biopsies showed microscopic colitis. There are limited reports of the use of teriparatide in post operative hypoparathyroidism in adults. Teriparatide was utilized in a study of children with hypoparathyoidism and malabsorption.3 The use of teriparatide after thyroid surgery resulting in either permanent or temporary postoperative hypoparathyroidism reduced hospitalization duration 2 and, in a 2-year prospective study teriparatide was noted to improve quality of life parameters in patients with post surgical hypoparathyroidism.4